Increasing photoluminescence yield of CsPbCl3 nanocrystals by heterovalent doping with Pr3+. (September 2020) - Ma, Jinjin; McLeod, John A.; Chang, Lo-Yueh; Pao, Chih-Wen; Lin, Bi-Hsuan; Li, Xiao-Yun; Wang, Zhiqiang; Chen, Jiatang; Sham, Tsun-Kong; Liu, Lijia
Highlights: Heterovalent doping with Pr 3+ enhances the photoluminescence of CsPbCl3 . Dual near-band gap emissions are present in almost all perovskite nanocrystals. Adding PrCl3 fills the Cl-vacancy, but over-coordination leads to PL decrease. Pr 3+ adds donor states to CsPbCl3 and improves its electronic properties. Graphical abstract: Abstract: CsPbCl3 perovskite nanocrystals are doped with heterovalent Pr 3+ using hot-injection method. These Pr 3+ -doped CsPbCl3 nanocrystals exhibit a dramatically improved absolute photoluminescence quantum yield (PLQY) compared to the undoped CsPbCl3, reaching 78.9 % PLQY at 9 % Pr-substitution. The crystal structure modification upon Pr 3+ doping and luminescence mechanism are investigated using conventional optical spectroscopy and synchrotron X-ray spectroscopy (i.e., X-ray absorption fine structure and X-ray excited optical luminescence). Both the Pr 3+ and Cl − are found contributing to the luminescence enhancement, and their individual roles in luminescence enhancement are analyzed.